Thoreau at Walden - Thoreau, Henry David, 1817-1862.; Porcellino, John.; Thoreau, Henry David, 1817-1862.; Center for Cartoon Studies (New York : Hyperion, 2008)
A graphic novel interpretation of Henry David Thoreau's "Walden," featuring the actual words from the text in which Thoreau describes his experiment in simple living.
Other title: Center for Cartoon Studies presents Thoreau at Walden.
Includes bibliographical references (p. 99).
Booklist.
Kirkus Starred.
School Library Journal.
6.6
Keywords: Thoreau, Henry David, -- 1817-1862 -- Homes and haunts -- Massachusetts -- Walden Woods -- Comic books, strips, etc; Thoreau, Henry David, -- 1817-1862 -- Philosophy -- Comic books, strips, etc; Thoreau, Henry David, -- 1817-1862.; Thoreau, Henry David, -- 1817-1862 -- Homes and haunts -- Massachusetts -- Walden Woods; Thoreau, Henry David, -- 1817-1862.; Thoreau, Henry David, -- 1817-1862 -- Homes -- Walden Woods (Mass.); Cartoons and comics; Comic books, strips, etc; Walden Woods (Mass.) -- Social life and customs -- Comic books, strips, etc; Walden Woods (Mass.) -- Social life and customs; Walden Woods (Mass.)